Administrativa bördor? - Skripkin, Anastasia; Johanesson, Simon (My University, 2013)
At this point seamen have a lot of tasks of administrative character, beyond the traditional tasks aboard a ship. Due to the new conventions that are formed by IMO, more requirements are added which often lead to time consuming administrative tasks and documentation that should be spent on activities which are contributing to the ships safety. The issue has been observed by IMO that has through BIMCO done a study with the aim to identify and reduce administrative burdens at sea. The primary aim of this study is to find out if safety officers aboard Swedish ferries consider that SOLAS Chapter III, 8.3 och 19.5 regulations are administrative burdens, restricted to muster lists and documentation of training aboard the ship. The secondary questions to the study are if it is possible to remove, combine or change the documents and how much time can be saved by doing this. The question about timesaving could not be answered, because the values were scattered and could not be used for further investigation. The observed values were accumulated by a survey and the result indicated that safety officers did not experience the two regulations as administrative burdens. Due to this, the majority of the respondents did not have requests about changing or removing the requirements since all safety officers considered them to be important. Other duties that were experienced as administrative burdens were customs lists, handling of certificates and reporting to various authorities.
Keywords: Transportteknik och logistik; Arbetslivsstudier; Transport Systems and Logistics; Work Sciences